You are on page 1of 8

# ECEN 314: Signals and Systems

Solutions to HW 3 Problem 1.27 (a) y(t) = x(t − 2) + x(2 − t) Let us check for linearity. x1 (t) → y1 (t) = x1 (t − 2) + x1 (2 − t) x2 (t) → y2 (t) = x2 (t − 2) + x2 (2 − t) ax1 (t) + bx2 (t) = x3 (t) → y3 (t) = x3 (t − 2) + x3 (2 − t) = ax1 (t − 2) + bx2 (t − 2) + ax1 (2 − t) + bx2 (2 − t) = a(x1 (t − 2) + x1 (2 − t)) + b(x2 (t − 2) + x2 (2 − t)) = ay1 (t) + by2 (t) Hence linear. Let us check for time-invariance. x1 (t) → y1 (t) = x1 (t − 2) + x1 (2 − t) x1 (t − to ) = x2 (t) → y2 (t) = x2 (t − 2) + x2 (2 − t) = x1 (t − to − 2) + x2 (2 − t − to ) = y1 (t − to ) Note that y1 (t − to ) = x1 (t − to − 2) + x1 (2 − t + to ). Hence time-variant. Suppose |x(t)| < B. Then y(t) < B + B = 2B (because |x(t − 2)| < B and |x(2 − t)| < B). Hence stable. Not memoryless as the present output at time t depends on t − 2. Non-Causal because y(-1)=x(-3)+x(3). So depends on future inputs.

(b) y(t) = [cos(3t)]x(t)

1

x1 (t) → y1 (t) = [cos(3t)]x1 (t) x1 (t − to ) = x2 (t) → y2 (t) = [cos(3t)]x2 (t) = [cos(3t)]x1 (t − to ) = y1 (t − to ) Note that y1 (t − to ) = [cos(3(t − to ))]x1 (t − to ).Let us check for linearity. x1 (t) → y1 (t) = [cos(3t)]x1 (t) x2 (t) → y2 (t) = [cos(3t)]x2 (t) ax1 (t) + bx2 (t) = x3 (t) → y3 (t) = [cos(3t)]x3 (t) = [cos(3t)] ax1 (t) + bx2 (t) = ay1 (t) + by2 (t) Hence linear. Memoryless as the output at time t depends only on inputs at time t. 2t x1 (t) → y1 (t) = −∞ 2t x1 (τ )dτ x2 (t) → y2 (t) = −∞ 2t x2 (τ )dτ ax1 (t) + bx2 (t) = x3 (t) → y3 (t) = −∞ x3 (τ )dτ 2 . Clearly causal. Hence time-variant. Let us check for time-invariance. when |x(t)| < B. 2t (c) y(t) = −∞ x(τ )dτ Let us check for linearity. Stable as |y(t)| < ∞.

y(1) depends on the value of x(t) at t = 2. 2t x1 (t) → y1 (t) = −∞ 2t x1 (τ )dτ x1 (t − to ) = x2 (t) → y2 (t) = −∞ 2t x2 (τ )dτ = −∞ x1 (τ − to )dτ 2t−to = −∞ x1 (τ )dτ = y1 (t − to ) 2(t−to ) Note that y1 (t − to ) = −∞ x1 (τ )dτ . causal and stable and 3 . Suppose x(t) = 1. Let us check for time-invariance. x(t) + x(t − 2) t ≥ 0 (d) y(t) = By using the same method as we used for the above parts. Hence time-variant. it is linear. 2 Non-causal because. Hence unstable. as y(1) = −∞ x1 (τ )dτ . Then y(1) = ∞.2t = −∞ 2t ax1 (τ ) + bx2 (τ ) dτ 2t = a −∞ x1 (τ )dτ + b −∞ x2 (τ )dτ = ay1 (t) + by2 (t) Hence linear. Clearly has memory by the above argument. 0 t<0 .

It is non-causal as well. If the system is linear. stable. where y2 (t) is the output to the input x2 (t). Suppose let the input be x1 (t) = 1 for all t. Let us see whether it is time-invariant. x(t) + x(t − 2) x(t) ≥ 0 By using the same technique as was used for the previous problems. 3 . this is time-invariant. x1 (t) → y1 (t) = x1 (t − to ) = x2 (t) → y2 (t) = = 0 t<0 x1 (t) + x1 (t − 2) t ≥ 0 0 t<0 x2 (t) + x2 (t − 2) t ≥ 0 0 t<0 x1 (t − to ) + x1 (t − to − 2) t ≥ 0 = y1 (t − to ) This is because y1 (t − to ) = Hence time-variant. ∀ t Let us now take the input x2 (t) = −x1 (t) = −1. (f) y(t) = x(t/3) This is linear and stable. It is not memoryless (for example. causal. Let us check for linearity. 0 t < to x1 (t − to ) + x2 (t − to − 2) t ≥ to (e) y(t) = 0 x(t) < 0 . Since x2 (t) < 0. Then the output y1 (t) corresponding to the input x1 (t) is y1 (t) = 2. not memoryless. the output y2 (t) = 0 = −y1 (t). then we should get y2 (t) = −y1 (t) = −2. Hence not linear. the output at time t = −3 depends on input at t = −1). Now let us check for time-invariance. x1 (t) → y1 (t) = x1 (t/3) x1 (t − to ) = x2 (t) → y2 (t) = x2 (t/3) t = x1 − to 3 = y1 (t − to ) This is because y1 (t − to ) = x1 4 t − to .not memoryless.

causal. This is stable as |y[n]| < ∞. Hence time-variant. dx(t) dt (g) y(t) = This is linear. This is not memoryless. it is linear. if |x[n]| < B.28 (a) y[n] = x[−n] Let us check for linearity. This is not memoryless as y(t) depends on x(t − δt) in calculating dx(t) . Non-causal because. Clearly has memory by the above argument. Let us check for time-invariance.Hence time-variant. stable. y[−1] depends on the value of x[1]. x1 [n] → y1 [n] = x1 [−n] x1 [n − no ] = x2 [n] → y2 [n] = x2 [−n] = x1 [−n − no ] = y1 [n − no ] Note that y1 [n − no ] = x1 [−n + no ]. (b) y[n] = x[n − 2] − 2x[n − 8] By using the same technique as used for the above problem. since dx(t) = limδt→0 x(t)−x(t−δt) . as well as time-invariant. x1 [n] → y1 [n] = x1 [−n] x2 [n] → y2 [n] = x2 [−n] ax1 [n] + bx2 [n] = x3 [n] → y3 [n] = x3 [−n] = ax1 [−n] + bx2 [−n] = ay1 [n] + by2 [n] Hence linear. dt dt δt Problem 1. 5 . time-invariant.

(c) y[n] = nx[n] x1 [n] → y1 [n] = nx1 [n] x2 [n] → y2 [n] = nx2 [n] ax1 [n] + bx2 [n] = x3 [n] → y3 [n] = nx3 [n] = n(ax1 [n] + bx2 [n]) = ay1 [n] + by2 [n] Hence linear. not memoryless. non-causal. Hence time-variant. where E is the even part.   (e) y[n] = x[n] n≥1 0 n=0 . Let us check for time-invariance. This is not stable because if x[n] = 1 for all n. Let us check for time-invariance. not memoryless and non-causal. Memoryless because. then y[n] → ∞ as n → ∞. This is time-variant which can be seen by using exactly the same steps as we used for Problem 1.27 (a) with t replaced by n. It is also causal. 6 . y[n] depends only on x[n]. x1 [n] → y1 [n] = nx1 [n] x1 [n − no ] = x2 [n] → y2 [n] = nx2 [n] = nx1 [n − no ] = y1 [n − no ] Note that y1 [n − no ] = (n − no )x1 [n − no ]. stable. E{x[n − 1]} = x[n − 1] + x[1 − n] 2 This is linear.  x[n + 1] n ≤ −1 This is linear and stable. (d) y[n] = E{x[n − 1]}.

28 (e) that it is linear and time-variant. Let us check for time-invariance.31 7 .x1 [n] → x1 [n − no ] = x2 [n] → = = This is because y1 [n − no ] = Hence time-variant. (f) y[n] =  x[n] n ≤ −1 Following exactly the same steps.   x1 [n] n≥1 0 n=0 y1 [n] =  x1 [n + 1] n ≤ −1  n≥1  x2 [n] 0 n=0 y2 [n] =  x2 [n + 1] n ≤ −1  n≥1  x1 [n − no ] 0 n=0  x1 [n + 1 − no ] n ≤ −1 y1 [n − no ]   x1 [n − no ] n ≥ no + 1 0 n = no  x1 [n + 1 − no ] n ≤ no − 1   x[n] n ≥ 1 0 n=0 . Hence time-variant. It is causal. it is easy to see from Problem 1. memoryless and stable. x1 [n] → y1 [n] = x1 [4n + 1] x1 [n − no ] = x2 [n] → y2 [n] = x2 [4n + 1] = x1 [4n + 1 − no ] = y1 [n − no ] This is because y1 [n − no ] = x[4(n − no ) + 1] = x1 [4n − 4no + 1]. (g) y[n] = x[4n + 1] This system is linear as well as stable. Further it is non-causal and memoryless. Problem 1.

then x[n] = ej2πn(p/q) . 8 .35). This implies that (T /To ) = k/N = rational number ⇒ (b) If T /To = p/q.36 (a) If x[n] is periodic ejωo (n+N )T =e (2π/To )N T = 2πk jωo nT . See the ﬁgure below. q) = gcd(p. q) (from Problem 1.(a) Note that x2 (t) = x1 (t)−x1 (t−2). Therefore using linearity we get y2 (t) = y1 (t)−y1 (t−2). q) = gcd(p. (b) We see that x3 (t) = x1 (t + 1) + x1 (t). y1 (t + 1) + y1 (t). where ωo = 2π/To . and therefore the fundamental frequency is 2π 2π p ωo T gcd(p. q) q p q p (c) From part (b) above. q) periods of x(t) are needed to form a single period of x[n]. Then the fundamental period is q/gcd(p. See the ﬁgure below. p/gcd(p. Therefore using linearity we get y3 (t) = y(t) 2 2 y(t) 3 0 −2 2 4 t −1 1 2 t Problem 1.